ANALISIS PENGENDALIAN MUTU PROSES PRODUKSI AIR MINUM DALAM KEMASAN MEREK OASIS PADA PT. OASIS WATERS INTERNASIONAL - Hadidu Hadidu (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aims to identify and analyze the quality control of the production process of bottled water brand OASIS in accordance with the Indonesian National Standard (SNI) with the method used is the analysis of cause and effect diagram is used to analyze the problem and the factors that cause the problem . In this study the causal diagram is used to analyze the factors that affect the quality of bottled water, which analyzed the results of brainstorming with the company that is the owne , qualitycontrol (QC), and employee/production operato, X and R control charts (range) is used to analyze the data in the chart control. Average (X) is the most useful measure of central tendency. Variability or dispersion process can be controlled with a control chart for standard deviation, which is called the graph S, or a control chart for the range called the graph of R. The range is the difference between the lowest and highest measurement results in a single row. This method is used to describe variasim or storage that occurs in converging trends and dissemination of observation Results Discussion on quality control of the production process of bottled water brand OASIS at PT. Oasis International Waters in Makassar, it can be obtained is that based on the results penggujian pH, TDS, and turbidity indicates that the quality of bottled water brand OASIS, has met the Indonesian National Standard (SNI) .